Finite-element analyses of light timber-framed walls with and without openings - Toğay, Abdullah; Isleyen, Ummu Karagoz; Ediz, Ibrahim; Durucan, Cengi̇zhan; Anil, Özgür (Emerald, 2017)
The static responses of timber-framed shear walls with and without openings of variable dimensions and locations were numerically investigated using the finite-element (FE) method. The lateral load resistance capacities and general load–displacement behaviours of the timber-framed shear walls were investigated. In the FE study, the frame elements were modelled as beams, plates were modelled as shells and nails were modelled as spring elements. The plastic behaviour of the materials was modelled using experimental stress–strain relationships of the materials. For timber frames and oriented strand board (OSB) panels, uniaxial stress–strain curves were experimentally obtained under tensile and compressive loading. From the experimental materials models it was found that spruce exhibited non-linear behaviour under both tensile and compressive stress. In contrast, the OSB sheathing layer used in the analyses exhibited non-linear behaviour under compressive stress and linear behaviour under tensile stress. The numerical results were verified using experimental load–deflection relationships obtained from a previous study. Good agreement was found between the analytical and experimental results. To further examine the applicability of the experimentally verified numerical model, four different timber-framed shear walls were simulated with FE models.